William Schouler correspondence - Schouler, William, 1814-1872.
Photocopy of a transcript of a letter (1864 September 2) written by Schouler, adjutant general of Massachusetts, to Gov. John A. Andrew concerning a request of James O. Newhall and a photocopy of Andrew's reply (1864 September 24). Both letters mention the sacrifices of Lydia Parker Bixby whose five sons died while serving in the Union Army during the Civil War.
Negative photocopies.
Journalist, historian, and public official of Massachusetts.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Andrew, John A. -- 1818-1867 -- Correspondence; Bixby, Lydia Parker, -- 1801?-1878.; Newhall, James O; Massachusetts -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Casualties; Historians; Journalists; Public officials -- Massachusetts